The SAGE handbook of race and ethnic studies - Solomos, John; Hill Collins, Patricia (London ; Thousand Oaks, Calif. : SAGE, 2010)
What is the state of race and ethnic studies today? How has the field emerged? What are the core concepts, debates and issues? This panoramic, critical survey of the field supplies researchers and students with a vital resource
Situating race and ethnic studies / Patricia Hill Collins and John Solomos -- Theorising race and ethnicity : contemporary paradigms and perspectives / Caroline Knowles -- Studying'race' and ethnicity : dominant and marginalised discourses in the critical North American case / Joe R. Feagin and Eileen O'Brien -- Researching race and ethnicity : methodological issues / Nancy A. Denton and Glenn D. Deane -- The spirit lives on : races and disciplines / Chetan Bhatt -- Racism, class and the dialectics of social transformation / Satnam Virdee -- The nexus of race and gender : parallels, linkages, and divergences in race and gender studies / Margaret L. Andersen -- Ethnicities and sexualities / Joane Nagel -- Nation and post-nation : nationalism, transnationalism and intersections of belonging / Floya Anthias -- Multiculturalism and racial democracy : state policies and social practices / Peter Kivisto -- Law, critical race theory and related scholarship / Athena D. Mutua -- Ethnic conflict / Ralph Premdas -- Globalisation, migration and citizenship / Liza Schuster -- The family as a race institution / Maxine Baca Zinn -- Race, ethnicity and education : the search for explanations / James A. Banks and Caryn Park -- Still the'most segregated hour' : religion, race and the American experience / Cheryl Townsend Gilkes -- Whiteness in the dramaturgy of racism / Les Back -- No longer invisible : Afro-Latin political mobilisation / Michael G. Hanchard and Mark Q. Sawyer -- Diaspora and hybridity / Claire Alexander -- Issues for the twenty-first century / Patricia Hill Collins and John Solomos
Includes bibliographical references and index
Keywords: Race relations; Ethnic relations; Race relations -- Research; Society